Pelaksanaan Program Infeksi Menular Seksual oleh Perawat Pemasyarakatan di Lapas Jawa Tengah: Studi Kasus - Maria Desyline; Muhamad Muin; Megah Andriany (Journal of Telenursing (JOTING), 2022)
This study aims to explore implementing the STI program carried out by correctional nurses in Central Java. The method used is qualitative. The results showed three themes regarding implementing the STI program in prisons: screening of WBP with STIs, the constraints of correctional nurses in the STI program, and strategies for correctional nurses to overcome obstacles. In conclusion, correctional nurses must screen STIs on all inmates who enter prisons and when inmates have complaints about STIs. Keywords: Correctional Institution, Correctional Nurse, Sexually Transmitted Infection Program